A linguistic postulate of Quechua - Carpenter, Lawrence K. (1987)
When analyzing any language, there are certain categories and ways of conceiving that can occur at various levels with great frequency. Many times, these categories are so universal and self-evident that they show up not only linguistically but have cultural correspondences as well. Such recursive and inclusive themes are called 'linguistic postulates' (Hardman, 1978). While I was carrying out an investigation of the Quichua dialects spoken in Ecuador, I noticed that certain postulates were evident in all the dialect areas that I studied.